Parliamentary representatives in old Poland. Envoys, mandataries, and nation’s representatives - Uruszczak, Wacław (Czasopismo Prawno-Historyczne, 2021)
Parliamentary representatives in old Poland. Envoys, mandataries, and nation’s representatives